Interspecific competition promotes habitat and morphological divergence in a secondary contact zone between two hybridizing songbirds - Sottas, Camille; Reif, Jiří; Kuczyński, Lechosław; Reifová, Radka (Journal of evolutionary biology, 2018)
Interspecific competition is assumed to play an important role in the ecological differentiation of species and speciation. However, empirical evidence for competition's role in speciation remains surprisingly scarce. Here, we studied the role of interspecific competition in the ecological differentiation and speciation of two closely related songbird species, the Common Nightingale (Luscinia megarhynchos) and the Thrush Nightingale (Luscinia luscinia). Both species are insectivorous and ecologically very similar. They hybridize in a secondary contact zone, which is a mosaic of sites where both species co-occur (syntopy) and sites where only one species is present (allotopy). We analysed fine-scale habitat data for both species in both syntopic and allotopic sites and looked for associations between habitat use and bill morphology, which have been previously shown to be more divergent in sympatry than in allopatry. We found that the two nightingale species differ in habitat use in allotopic sites, where L. megarhynchos occurred in drier habitats and at slightly higher elevations, but not in syntopic sites. Birds from allotopic sites also showed higher interspecific divergence in relative bill size compared to birds from syntopic sites. Finally, we found an association between bill morphology and elevation. Our results are consistent with the view that interspecific competition in nightingales has resulted in partial habitat segregation in sympatry and that the habitat-specific food supply has in turn very likely led to bill size divergence. Such ecological divergence may enhance prezygotic as well as extrinsic postzygotic isolation and thus accelerate the completion of the speciation process.
Keywords: stravovací zvyklosti; birds; vznik druhů (genetika); feeding niche; Hybridization, Genetic; habitat segregation; Ecosystem; Luscinia; Songbirds; Beak; rozšíření zvířat; zvířata; Animal Distribution; hybridizace genetická; genetická variace; ecological speciation; Genetic Variation; Altitude; Genetic Speciation; zpěvní ptáci; Animals; Feeding Behavior; interspecific competition; ekosystém; zobák; nadmořská výška